(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In this article the data of morphometric studies of caries conducted among young men living in Khorezm region. 514 boys and girls of schoolchildren aged 11 to 17 years living in the city of Urgench were studied, morphometric studies of caries detected in the subjects were conducted and analyzed.